Frequency of Beijing family of Mycobacterium tuberculosis in Mashhad, Northeast of Iran - Mirbagheri, Seyedeh Zohre; Meshkat, Zahra; Naderinasab, Mahboubeh; Ghadamsoltani, Toktam; Rostami, Sina; Momen Heravi, Mastoureh; Askari, Vahid Reza (Archives of Medical Laboratory Sciences, 2019)
Background: Beijing family of Mycobacterium tuberculosis (M. tuberculosis) is widespread in Asia and has been involved in outbreaks of multidrug-resistant tuberculosis in various parts of the world. The aim of the current study was to evaluate the frequency of Beijing family of M. tuberculosis in patients with tuberculosis in Mashhad, Iran. Materials and Methods: Totally, 72 specimens of M. tuberculosis were collected from pulmonary samples of patients at Ghaem hospital in Mashhad (Iran) between April 2011 and May 2012. The authors used IS6110-based polymerase chain reaction (IS6110-based PCR) method to identify Beijing family of M. tuberculosis. Based on PCR results, strains belonging to Beijing and non-Beijing families were detected. Also, among members of Beijing family, ancient and modern subfamilies were distinguished. Results: Beijing genotype was observed in five (6.9%) of 72 culture positive samples. In the present study, no cases of modern subfamilies were detected. M. tuberculosis had a higher frequency in men (61.1%) compared to that of women (38.9%). Our data demonstrated that IS6110-based PCR can be used to distinguish Beijing family from non-Beijing family, with high specificity and sensitivity. Conclusion: The improvement of convenient and quick methods to detect and control Beijing family of M. tuberculosis in clinical samples is an interesting subject in areas where M. tuberculosis is prevalent. This method has the advantages of being quick, cost-effective, and requires comparatively less clinical laboratory equipment.